PEMBELAJARAN OPERASI HITUNG BILANGAN CACAH DENGAN PENDEKATAN REALISTIK PADA MATA KULIAH PEMBELAJARAN PEMECAHAN MASALAH MATEMATIKA - P. Sarjiman P. Sarjiman (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2010)
The aim of this research were : (1) to raise the students' understanding in learning the counting operation concept of the whole number and the method of learning process by realistic approach; (2) to know how the process of learning by realistic approach and students' response towards the learning model. The method of research used was the classroom action research with the qualitative atmosphere. The research steps consisted of planning, action, observation and reflection. The data were analized by interpretative qualitative for the qualitative data and by descriptive statistics for the quantitative data. The learning by realistic approach in this research was carried out in two cycles; the first cycle was only one occurance and also for the second cycle. In the first cycle the result was not satisfying; the mean score of the test after the action carried out was only 51,52, though at the previous condition the mean score was only 40,611; where as the second cycle the result of the test after the action carried out had been 75,55. In the first cycle, the students'response and the class management had not been in accordance with the researchers'hope and the criteria stated. It was different from the second cycle; the process of the learning had been running well in accordance with the criteria stated. So is the case with the students'response; it showed that everything was good and positive. Key Words: The Concept of Whole Number and the Learning by Realistic Approach